PENGARUH LINGKUNGAN KERJA NON FISIK TERHADAP KEPUASAN KERJA DOSEN TETAP STUDI PADA FAKULTAS KOMUNIKASI DAN BISNIS UNIVERSITAS TELKOM BANDUNG - Pangarso, Astadi; Ramadhyanti, Vidi (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2015)
The purpose of this study is to determine the influence of non-physical work environment on job satisfactionÃ‚Â lecturer of the Faculty of Communication and Business at the University of Telkom Bandung. The independentvariable X of the study is non-physical work environment while the dependent variable Y is job satisfaction. TheÃ‚Â data are obtained by distributing questionnaires, sampling technique uses the saturation. The analytical methodÃ‚Â used is a simple linear regression analysis method.The research results prove that the non-physical work environment by 38.8% have influence on jobÃ‚Â satisfaction lecturer of the Faculty of Communication and Business, University of Telkom Bandung and theremaining 61.2% is influenced by other factors that are not observed in this study. In other words, there isÃ‚Â a partial effect of non-physical work environment on permanent lecturersÃ¢â‚¬â„¢ job satisfaction on the Faculty ofCommunication and Business, University of Telkom Bandung.Keywords: human resources, non-physical work environment, job satisfaction